Head and Neck Congenital Anomalies in Neonate Hospitals in Hail, Saudi Arabia - Assiry, Ali A (Int J Clin Pediatr Dent, 2020)
INTRODUCTION: There is secrecy in the literature published about congenital anomalies of head and neck. Dentists may encounter with many head and neck anomalies during their practice. This study aimed to assess the prevalence of head and neck anomalies among all congenital anomalies and to identify risk factors associated with head and neck anomalies. MATERIALS AND METHODS: A cross-sectional hospital-based study was conducted on neonate data available in the records of neonate hospitals in Hail; records from 1432 to 1438 in Hijri Islamic calendar (equivalent to 2010–2016) were employed. All neonates from birth to 28 days after, who were born or admitted to these hospitals, were included in this study. RESULTS: The prevalence of head and neck anomalies among all congenital anomalies was 5.5%. The highest incidence rate was found in year 1435 (Islamic Hijri Year), in which the incidence rate was 7.1%. Cross tabulation between demographic characteristics and head and neck anomalies revealed that sex of the neonates was significantly associated with head and neck anomalies. The birth weight of the surveyed neonates and consanguinity marriage of the parents had no significant association with head and neck anomalies. CONCLUSION: The occurrence of head and neck anomalies showed a wide variation in different years, and the prevalence among other anomalies is associated significantly with sex of newborn. HOW TO CITE THIS ARTICLE: Assiry AA, Khan SD, Al-Shubrmi HR, et al. Head and Neck Congenital Anomalies in Neonate Hospitals in Hail, Saudi Arabia. Int J Clin Pediatr Dent 2020;13(2):160–162.